Methodology of directional asymmetry adjustment in facial asymmetry measurements of long-tailed macaques. - Kirk, Yvonne Hui Min. (2010)
Facial asymmetries consist of fluctuating asymmetry, directional asymmetry, and antisymmetry. Measurements in facial asymmetry studies may be inaccurate in the presence of directional asymmetry (DA) as DA have genetic basis. This paper explores the methodology of DA adjustment in facial asymmetry measurements of 22 long-tailed macaques (Macaca fascicularis). 3 methods of asymmetry measurements were used; an online program and two templates of manual measurements. DA was found to be present in one template of manual measurements. After adjustment for DA, high correlation of asymmetry results between manual measurements was found. There were no significant correlation of asymmetry results between manual measurements and the online program. ANOVA tests did not find any significant differences in the asymmetry scores between the three methods of measurements.